2002
DOI: 10.1128/jvi.76.11.5326-5338.2002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Sequences in the 3′ Nontranslated Region of Hepatitis C Virus That Are Important for RNA Replication

Abstract: The genome of the hepatitis C virus (HCV) is a plus-strand RNA molecule that carries a single long open reading frame. It is flanked at either end by highly conserved nontranslated regions (NTRs) that mediate crucial steps in the viral life cycle. The 3 NTR of HCV has a tripartite structure composed of an about 40-nucleotide variable region, a poly(U/UC) tract that has a heterogeneous length, and a highly conserved 98-nucleotide 3-terminal sequence designated the X tail or 3X. Conflicting data as to the role t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
250
3
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(266 citation statements)
references
References 64 publications
9
250
3
4
Order By: Relevance
“…As this overlaps with the IRES, there is considerable interest in understanding how this region might modulate translation and replication, which are unlikely to occur simultaneously on the same RNA template. The 3፱ NCR has been found to contain a nonessential variable region, a poly-U/UC tract that must be more than 26 nucleotides long, followed by a highly conserved and essential 3፱X domain 55,57,76 . Recently a conserved stem-loop structure within the NS5B coding region, 5BSL3.2, was found to be required for RNA replication 78 .…”
Section: Mechanisms Of Hcv Rna Replicationmentioning
confidence: 99%
“…As this overlaps with the IRES, there is considerable interest in understanding how this region might modulate translation and replication, which are unlikely to occur simultaneously on the same RNA template. The 3፱ NCR has been found to contain a nonessential variable region, a poly-U/UC tract that must be more than 26 nucleotides long, followed by a highly conserved and essential 3፱X domain 55,57,76 . Recently a conserved stem-loop structure within the NS5B coding region, 5BSL3.2, was found to be required for RNA replication 78 .…”
Section: Mechanisms Of Hcv Rna Replicationmentioning
confidence: 99%
“…The HCV genome is a positivestranded Ϸ9.6-kb RNA molecule consisting of a single ORF, which is flanked by 5Ј and 3Ј untranslated regions (UTR). The HCV 5Ј UTR contains a highly structured internal ribosome entry site (3)(4)(5)(6)(7)(8), and the 3Ј UTR is essential for replication (9,10). The HCV ORF encodes a single 3,008-to 3,037-aa polyprotein that is posttranslationally processed to produce Ն10 different proteins: core protein, envelope proteins E1 and E2, p7, and nonstructural proteins NS2, NS3, NS4A, NS4B, NS5A, and NS5B (1,8,11).…”
mentioning
confidence: 99%
“…Mapping of cis-acting HCV RNA required for RNA synthesis both in vitro and in vivo indicated that the X-RNA is a minimal cis-acting RNA essential for HCV minus-strand RNA synthesis (Oh et al, 2000;Friebe and Bartenschlager, 2002). Furthermore, synthesis of minus-strand HCV RNA was shown to be initiated from the internal region of X-RNA with N-terminal (His)6 tagged full-length NS5B and E. coli lysyl-tRNA synthetase-fused NS5B (Oh et al, 2000;Kim et al, 2002).…”
Section: Introductionmentioning
confidence: 99%